Hubungan Kepercayaan Diri Siswa dengan Pemahaman Konsep Matematis Siswa Kelas XI MIA 1 SMAN 3 Lubuk Basung Kabupaten Agam - Vuve Ona Rahma Suci; Melisa .Melisa; Hamdunah .Hamdunah (Horizon, 2021)
The ability to understand concepts is one of the goals of mathematical ability. One of the factors for the lack of ability to understand concepts is self-confidence. This study aims to determine the relationship between students' self-confidence and understanding of mathematical concepts in class XI MIA SMAN 3 Lubuk Basung Kabupaten Agam.This study uses inferential research where inferential research is a study that tests a hypothesis, and relates one variable to another with quantitative analysis. The subjects of this study were students of class XI MIA 1 SMAN 3 Lubuk Basung. The research instrument used was a self-confidence questionnaire and a test for understanding mathematical concepts. The data analysis technique used is simple linear regression analysis and product moment correlation.Based on data analysis, the regression coefficient of the questionnaire score (b) is with a significant level of 0.05 because the regression coefficient (b) is positive, so there is a positive effect of X on Y. It means that the bigger X, the bigger Y on average. The close linear relationship between X and Y can be seen from the correlation coefficient r = where r approaches 1, then a positive linear relationship between X and Y so that it can be concluded that the bigger X, the greater Y and self-confidence has a positive influence on the ability to understand concepts of class XI students. MIA 1 SMAN 3 Lubuk Basung Kabupaten Agam.